Frozen ground and snow cover monitoring in the South Shetland Islands, Antarctica: instrumentation, effects on ground thermal behaviour and future research - De Pablo, M. A. (2016)
The study of the thermal behavior of permafrost and active layer on the South Shetland Islands, in the western side of the Antarctic Peninsula (Antarctica), has been our research topic since 1991, especially after 2006 when we established different active layer thickness and ground thermal monitoring sites of the CALM and GTN-P international networks of the International Permafrost Association. Along this period, the snow cover thickness did not change at those sites, but since 2010, we observed an elongation on the snow cover duration, with similar snow onset, but a delay on the snow offset. Due to the important effects of snow cover on the ground thermal behavior, we started in late 2015 a new research project (PERMASNOW) focused on the accurate monitoring of the snow cover (duration, density, snow water equivalent and distribution), from very different approaches, including new instrumentation, pictures analysis and remote sensing on optical and radar bands. Also, this interdisciplinary and international research team intends to compare the snow cover and ground thermal behavior with other monitoring sites in the Eastern Antarctic Peninsula where the snow cover is minimum and remains approximately constant.